On some Chrysometa Simon, 1894 species collected from Ecuador: redescription of C. bolivia, description of a new species, and comments on the type locality of C. otavalo (Araneae, Tetragnathidae) - Peñaherrera-R., Pedro (Zootaxa, 2025)
Chrysometa chuchaqui sp. nov is described from the valley of Tandayapa, Northwestern Ecuador, based on a unique character combination of male and female genitalia. C. bolivia Levi, 1986 is redescribed based on specimens from Ecuador, providing new information regarding the morphology of this species. Finally, the type locality of C. otavalo Levi, 1986 is discussed and a new georeferentiation is proposed.